2015
DOI: 10.1155/2015/384750
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Ischemic Stroke: Mechanistic Roles and Action

Abstract: Stroke is one of the most devastating neurological disabilities and brain's vulnerability towards it proves to be fatal and socio-economic loss of millions of people worldwide. Ischemic stroke remains at the center stage of it, because of its prevalence amongst the several other types attacking the brain. The various cascades of events that have been associated with stroke involve oxidative stress, excitotoxicity, mitochondrial dysfunction, upregulation of Ca2+ level, and so forth. Melatonin is a neurohormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 130 publications
0
55
1
Order By: Relevance
“…In the opinion of Escribano and co-worker [38], decrease of melatonin level in this pathology is a part of its pathogenic features. Thus, in cerebral ischemia melatonin reveals antioxidant, antiapoptotic and anti-inflammatory properties [39]. In ischemic stroke patients the impaired nocturnal melatonin excretion is associated with altered sleep-wake rhythm, increased blood cortisol level and decrease of T lymphocytes number [40].…”
Section: Brain Ischemiamentioning
confidence: 99%
“…In the opinion of Escribano and co-worker [38], decrease of melatonin level in this pathology is a part of its pathogenic features. Thus, in cerebral ischemia melatonin reveals antioxidant, antiapoptotic and anti-inflammatory properties [39]. In ischemic stroke patients the impaired nocturnal melatonin excretion is associated with altered sleep-wake rhythm, increased blood cortisol level and decrease of T lymphocytes number [40].…”
Section: Brain Ischemiamentioning
confidence: 99%
“…High levels of melatonin compared to other cellular compartments have been identified in mitochondria [24,25,26,27,28]. A variety of in vitro and in vivo studies have proven that melatonin targets mitochondria to reduce oxidative stress [29,30,31,32,33,34,35,36]. This results in decreased apoptosis, improved metabolic status, and an elevated survival rate of cultured cells, unicellular organisms, animals, and plants, which suffer with oxidative stress [37,38,39,40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Mel, a pineal hormone, as well as its metabolites, display important antioxidant properties in the nervous system [13, 14]. Mel has been previously recognized for its protective effects, which include properties related to radical scavenging and antioxidant potential [10].…”
Section: Introductionmentioning
confidence: 99%